Game Design as A Character Education Media For Children - Michael Marchiano (Journal of Business and Technology, 2021)
In the present era many children are contaminated with negative things from the internet due to lack of supervision from parents so that there are many verbal and nonverbal abuse. The many of children who do not behave according to age so that requires a character education media that can provide understanding of the character in the self, especially the self-confidence for children so as to be yourself and not fall into the negative.